PENGGUNAAN MEDIA POP UP BOOK DALAM PEMBELAJARAN PENDIDIKAN PANCASILA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS II SD GMIT NAMOSAIN - Juanita Aristia Wadu; Angelikus N. Koten; Treesly Y. N. Adoe (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The research entitled The Use of Pop up book Media in Pancasila Education Learning to Improve the Learning Outcomes of Second Grade Students of GMIT Namosain Elementary School is motivated by the learning outcomes of second grade students of GMIT Namosain Elementary School which are still relatively low. This was obtained from the results of initial observations conducted by researchers during PLP activities in second grade students of GMIT Namosain Elementary School, conditions were found related to the learning outcomes of second grade students related to Pancasila Education learning. Of the 31 students, 35.49% or as many as 11 students met the KKTP set by the school, while 64.51% or as many as 20 other students had not reached the KKTP. This study uses a Classroom Action Research (CAR) approach consisting of planning, implementation, observation and reflection stages. The data collection techniques used are observation and tests using research instruments including teacher observation sheets, student observation sheets, test questions, and documentation studies. The data analysis technique used is descriptive qualitative with percentage calculations (%). In cycle I, the percentage of students' mastery in cycle I was 58.06% and was included in the poor (K) category, but in cycle I the learning implemented was not successful. Meanwhile, the percentage of students' mastery in cycle II was 80.64% and was included in the good (B) category, so the learning was successful.